Role of financial development in economic growth in the light of asymmetric effects and financial efficiency - Shahbaz, Muhammad; Nasir, Muhammad A.; Lahiani, Amine (IDEAS Working Paper Series from RePEc, 2022)
The growth effects of financial development might be asymmetric and nonlinear according to the level of financialization of countries. As a corollary to this notion, in the subject study, we developed a three‐regime threshold autoregressive distributed lags (TARDL) model, which allows us to accommodate the asymmetric effect of financial development on economic growth in top 10 financially developed countries. We augmented the TARDL model by including trade openness, capital formation and labour as potential determinants of economic growth. The empirical findings revealed the existence of threshold asymmetric co‐integration between variables. In particular, in the upper regime, financial development boosts economic growth in Singapore while it exerts a negative impact on economic growth in Finland. In the middle regime, financial development increases economic growth in Australia and Singapore. However, in the lower regime, financial development hampers economic growth in the US, Malaysia and Singapore. Trade openness has a positive long‐run influence on economic growth in Canada, South Africa, Australia, Malaysia, New Zealand, Singapore, Finland and Norway. Capital formation strengthens economic growth in the US and Malaysia in the long‐run. Labour is found to sustain economic growth in the long‐run for Malaysia and Singapore. The dynamic multipliers which depict the response path of economic growth to a one‐unit shock of financial development in the three regimes highlight the discrepancies in the reaction of economic growth to financial development shocks occurring in different regimes. Important policy implications can be instigated from the empirical results.